ANALISIS KINERJA PENDINGINAN PASIF PADA PANEL SURYA MENGGUNAKAN PHASE CHAGE MATERIAL PARAFIN PADA BACK SHEET ALUMUNIUM - Andri Haris Setiawan; Suyanto; Ruri Agung Wahyuono (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The efficiency of the power generated by the solar panel will decrease as the temperature increases above the standart test conditions temperature on the surface of the solar panel. The decrease will reach 0.45% for every 10C increase. Cooling is required to prevent a drastic increase in temperature on the surface of the solar panel. Passive cooling using phase change materials is often used in an effort to keep the temperature of solar panels from getting too high. Based on this background, this study aims to analyze the effect of phase change paraffin material on an alumunium backsheet decreasing temperature and increasing the output power of solar panels. In this study, data collection used direct experimental methods with data analysis using quantitative and qualitative models. The results showed that the paraffin phase change material placed on an aluminum backsheet can reduce the temperature of the solar panel by 2.07% and increase the power output of the solar panel by 1.85%.